(untitled) (Medical Forum Monthly, 2024)
Background: Interlocking intramedullary nailing has become a popular method of fixation for closed tibial fractures, and a series of reports has confirmed excellent results with this technique. However, the use of intramedullary nails for open tibial fractures is controversial. The standard treatment for these injuries has been external fixation, particularly for fractures associated with more severe soft-tissue injuries. Objective: The purpose of the present study was to compare the clinical and radiographic results of intramedullary nailing of open fractures of the tibial shaft after reaming with those of nailing without reaming. Study Design: This was follow-up comparative study. Place and Duration of Study: This study was conducted at the Department of Orthopaedic, Shaikh Zayed Hospital, Lahore from Jan. 2009 to Dec. 2011. Materials and Methods: Thirty patients who had thirty-four open fractures of the tibial shaft were randomized into two treatment groups. Sixteen fractures (nine type-I, three type-II, two type-IIIA, and two type-IIIB fractures, according to the classification of Gustilo et al.) were treated with nailing after reaming, and eighteen fractures (ten type-I, four type-II, two type-IIIA, and two type-IIIB fractures) were treated with nailing without reaming. Result: The average diameter of the nail was 10 millimeters (range, nine to eleven millimeters) in the group treated with reaming and 9 millimeters (range, eight to ten millimeters) in the group treated without reaming. No clinically important differences were found between the two groups with regard to the technical aspects of the procedure or the rate of early postoperative complications. The average time to union was 30 weeks (range, thirteen to seventy-two weeks) in the group treated with reaming and 29 weeks (range, thirteen to fifty weeks) in the group treated without reaming. Two of the fractures treated with reaming and three of the fractures treated without reaming did not unite. There were two infections in the group treated with reaming and one in the group treated without reaming. More screws broke in the group treated without reaming four, per cent) than in the group treated with reaming (Three; 9 per cent). The functional outcome, in terms of pain in the knee, range of motion, return to work, and recreational activity, did not differ significantly between the groups. Conclusion: We concluded that the clinical and radiographic results of nailing after reaming are similar to those of nailing without reaming for fixation of open fractures of the tibial shaft, although more screws broke when reaming had not been done.